BMS-933043, a Selective α7 nAChR Partial Agonist for the Treatment of Cognitive Deficits Associated with Schizophrenia - King, Dalton (ACS Med Chem Lett, 2017)
[Image: see text] The therapeutic treatment of negative symptoms and cognitive dysfunction associated with schizophrenia is a significant unmet medical need. Preclinical literature indicates that α7 neuronal nicotinic acetylcholine (nACh) receptor agonists may provide an effective approach to treating cognitive dysfunction in schizophrenia. We report herein the discovery and evaluation of 1c (BMS-933043), a novel and potent α7 nACh receptor partial agonist with high selectivity against other nicotinic acetylcholine receptor subtypes (>100-fold) and the 5-HT(3A) receptor (>300-fold). In vivo activity was demonstrated in a preclinical model of cognitive impairment, mouse novel object recognition. BMS-933043 has completed Phase I clinical trials.